(untitled) (ESMAT Magazine, 2022)
In the present study, we will seek to explore the relationship between Law and Justice, considering, for this purpose, the constituent elements of Marxist social theory, among them the commodity and the value. The inspiration for the approach of the present article comes from the reflections coming from the classes of the Labor and Theory of Value in Marx subject, correlated to the project of the doctoral thesis of the author, which intends to shed light on the category of social (re)insertion within the Brazilian Prison System. The intended treatment is based on the Marxist categories of value and commodity, associated with the fundamental categories for the understanding of law in the order of the capital, such as subject, subject of law, and legal form, recommended by the Soviet jurist and author of the General Theory of Law and Marxism, Pachukanis. From the points of contact between these authors, promoted in this article, we will try to weave the first notes that lead to the approach we intend to defend in the thesis, whose hypothesis is based on the premise announced by Marx and Pachukanis, that, in the same way that value is attributed to the commodity, so is how it proceeds with the subject of law, whose classification as the holder of the right denotes the value attributed to him. In the light of the above, we consider the possibility of there being a direct relationship between what is posed as a right, and, therefore, value, to what is evoked as a right to (re)insertion / (re)socialization directed, in its virtuous majority, to people deprived of liberty who sine qua non are linked to the popular classes, composed of precarious workers and dissociated from the perspective of access to the right and the exercise of citizenship in its fullness.